Multicultural Values Representation in the English Textbook â€œEnglish in Mindâ€ for Junior High School - Rifdatul Habibah; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (Institut Agama Islam Negeri Palopo, 2024)
This research aims to look into the multicultural values represented in the Merdeka Curriculum textbook for Junior High School,